2017
DOI: 10.1371/journal.pone.0182948
|View full text |Cite
|
Sign up to set email alerts
|

Development of a technique for psyllium husk mucilage purification with simultaneous microencapsulation of curcumin

Abstract: This study focused on evaluating a technique for the psyllium husk mucilage (PHM) purification with simultaneous microencapsulation of curcumin. PHM was extracted with water and purified with ethanol. For the mucilage purification and simultaneous microencapsulation, an ethanolic solution of curcumin was used. After dehydration, the samples were analysed by instrumental techniques and evaluated for thermal stability. The presence of curcumin in the solution did not impair the yield of precipitated polysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…[24,25] PG is also widely used for constipation prevention, cholesterol reduction, intestinal regulation, film formation, wastewater treatment, and encapsulation of colourants (Figure S1). [26] The present research emphasized the green synthesis of PG-ZnO-NPs, which has not been reported. The PG-Zn-NPs are synthesized by evaporation and calcination and were characterized by various analytical techniques such as UV-Vis, FTIR, PL, and SEM-EDX.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…[24,25] PG is also widely used for constipation prevention, cholesterol reduction, intestinal regulation, film formation, wastewater treatment, and encapsulation of colourants (Figure S1). [26] The present research emphasized the green synthesis of PG-ZnO-NPs, which has not been reported. The PG-Zn-NPs are synthesized by evaporation and calcination and were characterized by various analytical techniques such as UV-Vis, FTIR, PL, and SEM-EDX.…”
Section: Introductionmentioning
confidence: 69%
“…[ 24,25 ] PG is also widely used for constipation prevention, cholesterol reduction, intestinal regulation, film formation, wastewater treatment, and encapsulation of colourants (Figure S1). [ 26 ]…”
Section: Introductionmentioning
confidence: 99%
“…The FT-IR spectrum of psyllium mucilage showed bands at 1726 cm −1 and 1649 cm −1 , whose are characteristics vibration of ester carbonyl group and carboxylic group [35] . The stretching vibration of C–O–C group was detected at 1049 cm −1 , suggesting the presence of arabinoxylans ( [35] ; Monge [42] ). In parallel, the konjac gum FT-IR spectra detected bands at 1730 and 1651 cm −1 with stretching vibrations that are characteristics assigned to acetyl groups (C=O) and the presence of amide groups (–CONH–), respectively [43] .…”
Section: Resultsmentioning
confidence: 99%
“…A rotary extractor was used to extract the ethanol from the precipitate. The spray drying technique was used for drying the samples [ 46 ]. After drying, the samples were stored in a well-closed container for further use.…”
Section: Methodsmentioning
confidence: 99%